India’s Changing Skies: Unravelling the Rise of Unpredictable Weather Extremes - Pranvi Sharma (International Journal of Climate Conditions, 2026)
India is currently experiencing a significant transformation in its climate system, characterized by rising temperatures, irregular rainfall patterns, and an increasing frequency of extreme weather events. These changes are no longer gradual or isolated but are becoming more visible and impactful across different regions of the country. This study provides a detailed examination of long-term climatic trends in India by analysing temperature variations, monsoon behaviour, and the growing occurrence of extreme events such as heatwaves, floods, and cyclones, with a focus on recent developments up to 2025–2026. The findings indicate that India’s climate is shifting from a relatively stable and predictable system to one marked by uncertainty and variability. One of the most notable changes is the rapid increase in temperatures, including a rise in night-time temperatures, which has serious implications for human health and energy consumption. Heatwaves are becoming more intense, frequent, and widespread, while new forms of climate stress, such as combined heat and humidity conditions, are emerging as major risks. At the same time, the monsoon system, which is crucial for India’s agriculture and water resources, is becoming increasingly erratic. Rainfall is now more concentrated in short periods, leading to floods, while long dry spells contribute to drought-like conditions. Oceanic factors, such as warming sea temperatures and marine heatwaves, are further influencing these patterns and adding to the complexity of climate behaviour. The study also highlights the wide-ranging socio-economic impacts of these changes, particularly on agriculture, water security, public health, and livelihoods. Vulnerable populations, including farmers and urban poor communities, are facing the greatest challenges. The paper emphasizes that climate change in India has become a continuous and systemic issue, requiring immediate attention. It concludes by stressing the importance of sustainable development, climate-resilient infrastructure, and effective policy measures to reduce risks and build long-term resilience.
Keywords: Climate change; Extreme Weather events; India climate trend; climate adaptation; heatwaves; monsoon variability; urbanization